Learning factory concept and development at Faculty of Industrial Management, Universiti Malaysia Pahang - Mohd Ghazali, Maarof; Nawanir, Gusman; Muhammad Fakhrul, Yusuf (KnE Social Sciences, 2019)
One of the key resources for the organization to sustain in the competitive business world is the employee’s competencies. Current business environment requires employees who are competent to adapt to ever-changing the business environment as a result of globalization and changes in customer’s requirement. The current teaching and training methods used in the universities is lacking a continuous delivery of competencies, especially in manufacturing education. One of the approaches that are becoming popular in developing student’s competencies is through the application of the learning factory concept. A learning factory represents a simulation of a real factory environment where students can gain hands-on the learning experience by conducting various projects. This paper will, therefore, present the process of setting up a learning factory and discuss how the learning factory can be used to support the teaching and learning process in a public technical university. This study was performed at the Faculty of Industrial Management, Universiti Malaysia Pahang. The purpose of the development of such a learning factory is to enable the students to attained hands-on experience on the concepts they have learned during class lecture and see how it can be applied in the real world.